Santri's Perception of Fast Food Halal Labels On Micro, Small and Medium Business Products - Dewi Mega Indah; Dapiah Dapiah; Mawar Jannati Al Fasiri (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
This study aims to find out the perception of halal labels on fast food products of small and medium business miro, among the students of the Kempek Cirebin Typical Islamic Boarding School in West Java and also to find out Fast Food according to an Islamic Perspective. In this study, the method used is a qualitative method. Qualitative methods are a type of method that produces discoveries that cannot be achieved (obtained) using statistical procedures or other methods of quantification (measurement). This method seeks to present data and facts about students' perception of halal labels on micro, small and medium business products in the Food Court of Kempek Cirebon Typical Islamic Boarding School, by means of observation, written interviews and in-depth interviews, documentation, and data triangulation. Based on the results of the research, it was found that there are still many perceptions of Santri towards the halal label of fast food MSME products, namely still considering that it is not too important to have a halal label on the food, because MSME products are products that are not packaged, not mass-produced, and the ingredients used are ingredients that are known to be halal or haram, and the manufacturing process can be seen directly by consumers. For example, fried rice and geprek chicken, and this statement is also strengthened by the results of the Head of the typical food court of kempek cirebon, and the Member of the MUI Fatwa Division, who explained that MSME Food Products do not matter if they are not labeled halal. Based on the results of the study, it can be concluded that the perception of students towards the halal label of fast food in Micro, Small and Medium Business products, that is, they still consider the halal label unnecessary.